Operating Experiences with an Advanced Fabric Energy Storage System - R.J Fuller (Australasian Journal of Construction Economics and Building, 2012)
Despite their proven track record in the cold climate countries of northern Europe, there are no reports in the research literature of experiences using advanced fabric energy storage (FES) systems in countries where cooling rather than heating is the main priority. This paper reports some of the experiences with the first known advanced FES system in Australia made over the first full calendar year of operation. It is located in a three-storey building on a university campus in Victoria and has been in operation since mid-2002. Temperature, energy use and operational mode data were recorded during 2003. Airflow measurements through the FES system have been made in five areas of the building. On-going operating problems still exist with the system and this has prevented a conclusive evaluation of its suitability for the southern Australian climate.